Structure perfection variations of Si crystals grown by Czochralski or floating zone methods after implantation of oxygen or neon atoms followed by annealing - Datsenko, L.I.; Auleytner, J.; Misiuk, A.; Klad'ko, V.P.; Machulin, V.F.; Bak-Misiuk, J.; Zymierska, D.; Antonova, I.V.; Melnyk, V.M.; Popov, V.P.; Czosnyka, T.; Choinski, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Structure perfection of the silicon crystals grown by the Czochralski and floating zone methods after implantation with oxygen or neon fast iones followed by annealing at the temperatures T ~ 1050-1150 ⁰0C, when large SiOx precipitates were formed, was studied by means of various X-ray diffraction methods. Considerable increments of integral reflectivities for different Bragg reflections of such samples in comparison with those calculated for a perfect crystal were detected. Broadening of the spatial intensity distribution curves for the Bragg-diffracted beams taken by a single crystal spectrometer as well as the maps of the diffuse isointensity distribution near a reciprocal lattice point, registered by the Philips high-resolution diffractometer, are shown. All of these diffraction effects related to creation of the SiOx precipitates formed on structural damages caused by implantation of oxygen or neon ions and subsequent annealing. Contrary to FZSi, where the appearence of SiOx precipitates was discovered due to intensive diffuse scattering near the layer contained the implanted oxygen ions only, in the case of CZSi samples with larger concentration of oxygen (up to 1*10¹⁸ at/cm³) such defects were formed not only near the burried layer, created by ions of oxygen or neon (with energy E = 4 MeV, dose 10¹⁴cm⁻²) but in a bulk of a crystal. Annealing of the FZSi crystals implanted by oxygen (E ~ 200 keV, dose ~ 10¹⁶-10¹⁷ cm⁻²) at enhanced hydrostatic pressure, additionally stimulated SiOx precipitation close to the implanted layer.